Forest-to-pasture conversion increases the diversity of the phylum Verrucomicrobia in Amazon rainforest soils - Ranjan, Kshitij; Paula, Fabiana S.; Mueller, Rebecca C.; Jesus, Ederson da C.; Cenciani, Karina; Bohannan, Brendan J. M.; Nüsslein, Klaus; Rodrigues, Jorge L. M. (Frontiers in Microbiology, 2015)
The Amazon rainforest is well known for its rich plant and animal diversity, but its bacterial diversity is virtually unexplored. Due to ongoing and widespread deforestation followed by conversion to agriculture, there is an urgent need to quantify the soil biological diversity within this tropical ecosystem. Given the abundance of the phylum Verrucomicrobia in soils, we targeted this group to examine its response to forest-to-pasture conversion. Both taxonomic and phylogenetic diversities were higher for pasture in comparison to primary and secondary forests. The community composition of Verrucomicrobia in pasture soils was significantly different from those of forests, with a 11.6% increase in the number of sequences belonging to Subphylum 3 and a proportional decrease in sequences belonging to the class Spartobacteria. Based on 99% OTU identity, 40% of the sequences have not been detected in previous studies, underscoring the limited knowledge regarding the diversity of microorganisms in tropical ecosystems. The abundance of Verrucomicrobia, measured with quantitative PCR, was strongly correlated with soil C content (r = 0.80, P = 0.0016), indicating their importance in metabolizing plant-derived carbon compounds in soils.